Pengembangan Media Pembelajaran Berbasis Android Pada Materi Sistem Persamaan Linier Dua Variabel Untuk Siswa Kelas VIII SPMN 2 Kupang - Yesri Jesika Teikuar; Juliana M. H. Nenohai; Damianus D. Samo (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2022)
Technological developments in the field of education require teachers to be more creative in creating technology-based learning media by utilizing Android. Therefore, this study aims to develop an Android on the material of a two-variable linear equation system for class VIII students of SMP Negeri 2 Kupang that is valid, practical and effective. The method used in this research is the R&D method and the model used is the ADDIE development model. The data collection techniques and instruments used are interviews, questionnaires and tests. The data analysis techniques used are field study analysis techniques, validity analysis techniques, practicality analysis techniques and effectiveness analysis techniques. The results showed that the developed media met the criteria of being valid, practical and effective. The average total validity by material experts is 4.58, practitioners are 4.65 and media experts are 4.25, â€œvery validâ€. The average total practicality of the teacher is 4.75 and the students where in the small class trial is 4.63, in the large class trial it is 4.43 "very practical". The percentage of completeness in small group trials obtained results of 100% "very effective", in large group trials obtained results of 81.25%, so android-based learning media is very feasible to use